Association between frailty index and epigenetic aging acceleration in older adults: Evidence from the health and retirement study - Xuhui Lin; Zhao Hu; Lu Tang; Yiqiang Zhan (Experimental Gerontology)
Backgound: This study aimed to examine the associations between the frailty index and four epigenetic aging acceleration (EAA) estimators in cross-sectional and longitudinal settings. Methods: The frailty index in the older adults was measured according to a cumulative health-deficit model. Four different epigenetic age measures (Hannum, PhenoAge, GrimAge, and DunedinPoAm38) were regressed against chronological age, and the resulting standardized residuals were indicative of EAA. The longitudinal relationship between EAA at baseline and changes in the frailty index during the 4-year follow-up were examined using a mixed linear model. Results: A single standard deviation (SD) increment in the frailty index was associated with a faster EAA, as indicated by the four clocks in Hannum (b = 0.057; P = 0.015), PhenoAge (b = 0.096; P < 0.001), GrimAge (b = 0.120; P < 0.001), and DunedinPoAm38 (b = 0.062; P = 0.002) in the fully adjusted model. A 1-SD increment in the GrimAge EAA was associated with a 0.003 frailty index increase (b = 0.003; P = 0.002). A 1-SD increment in DunedinPoAm38 EAA was associated with a 0.002 frailty index increase (b = 0.002; P = 0.009). Conclusions: The frailty index was cross-sectionally associated with EAA, while only GrimAge and DunedinPoAm38 EAA predicted changes in the frailty index. More research is needed to understand the interplay between pathways.